GRAMMATICAL ERRORS IN STUDENTS’ APPLICATION LETTERS: A CASE STUDY AT IPB INTERNASIONAL - Nova, Muhamad; Koerniawaty, Francisca Titing (IKIP Siliwangi, 2021)
In the professional sector, both spoken and written English communications become essential skills to be mastered by vocational students. However, as a non-native speaker, errors in writing are still faced as an obstacle for the students in applying their English capability. This research aimed at identifying the grammatical errors occurring in vocational students’ writing to overcome the error fossilization. The study was conducted in one vocational school in Denpasar, with a total of 45 students purposively selected. The study used a qualitative approach with a case study design. The data were gained by evaluating the students’ writing through an automated writing evaluation program and the type of writing evaluated in the study was application letter. Then, the data were analyzed through three phases; data reduction, data display, and conclusion drawing. As the result, there were 268 grammatical errors found in the students’ application letters. From their classifications, these errors were categorized into 17 types, with missing an article, misspelling, capitalization, incorrect number agreement, and incorrect preposition as the highest frequency of errors found. Keywords: Application Letter, Grammatical Errors, Vocational Education